Development of Technique for Rapid Extraction of Seeds from Cones of Pinus roxburghii Sarg. Under Controlled Conditions - Kumar, Dinesh; Srivastava, Shivendu K.; Negi, Surender Singh; Kumar, Pradeep (Indian Forester, 2006)
The conventional practice of extracting seeds from cones of P. roxburghii consists in drying of cones in the sun. This process takes about three weeks. A new technique has been developed which achieves seed extraction in four days. The new techniques involves soaking of cones in water for 10 minutes followed by drying at 60 Â° C for 11:50 hours and then shaking for few seconds every day. The technique did not show any adverse effect on seed germination. Further studies are in progress to adapt this technique so as to eliminate the need of kilns for practical application in forest nurseries.